2004
DOI: 10.1007/s00428-004-1143-9
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotype of lymphocytic infiltration in medullary carcinoma of the breast

Abstract: Medullary carcinoma (MC) of the breast is characterized by large anaplastic cells and infiltration by benign lymphocytes. Patients with this pattern of breast carcinoma are considered to have a better prognosis than those with other histological subtypes. We reviewed cases of primary breast carcinoma that were surgically resected between 1990 and 2004. Of these, 13 cases of medullary carcinoma of the breast with lymphocyte infiltration were reported. Tests for CD3, CD4, CD8, CD20, CD56, TIA-1, and granzyme B w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
37
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 17 publications
4
37
0
1
Order By: Relevance
“…It has also been reported that active CD8 þ cytotoxic T lymphocytes are the principal cells attacking breast carcinoma cells. [18][19][20] In medullary carcinoma of breast, our results strongly suggest that there is an active immune response against the tumor. Tumor infiltrating lymphocytes were typically present in both the stroma and within the epithelial nests of tumor cells.…”
Section: Discussionmentioning
confidence: 89%
“…It has also been reported that active CD8 þ cytotoxic T lymphocytes are the principal cells attacking breast carcinoma cells. [18][19][20] In medullary carcinoma of breast, our results strongly suggest that there is an active immune response against the tumor. Tumor infiltrating lymphocytes were typically present in both the stroma and within the epithelial nests of tumor cells.…”
Section: Discussionmentioning
confidence: 89%
“…For example, vaccination with her2/neu peptides induces specific cellular immunity in patients with breast cancer (31)(32)(33), and HER-2/neu vaccination may offer clinical benefit particularly in the setting of minimal residual disease (32,33). These findings underscore an increasing appreciation that, beyond melanoma and renal cell carcinoma, carcinomas of the breast can be targeted by cellular immunity (24,(28)(29)(30)34).…”
Section: Discussionmentioning
confidence: 98%
“…An association of GrB þ B cells with solid tumors has not been reported so far. However, while infiltration of certain tumors with B cells can be associated with a good prognosis (27)(28)(29)(30), in others the presence of B cells support a tumor-protective environment (31)(32)(33). We therefore hypothesized that GrB-expressing B cells may phenotypically represent Breg and may be present in the microenvironment of human tumors.…”
Section: Introductionmentioning
confidence: 99%